Digitalisasi Pelayanan Administrasi Kelurahan Melalui Penerapan Surat Digital (SURADI) - Larasati, Dewi Citra; Rohman, Abd. (REFORMASI, 2024)
The SURADI application is an official correspondence system in digital form. where this application is used as an information system Throughout the Malang City Regional Apparatus Organization, besides that at the sub-district level this application is the Regulation of the Minister of State for Administrative Reform and Bureaucratic Reform Number 6 of 2011 concerning Electronic Service Manuscripts in Government Environments. SURADI is designed to improve the city's script system, handle incoming and outgoing mail digitally, and optimize mail management within the government. The main objective of this research is to explore how the SURADI application contributes to improving administrative services. Based on the research that has been carried out, it is concluded that the digitalization of sub-district administration services through the application of Suradi has been carried out in the processing of letters such as cover letters, marriage transfer letters, marriage certificates, unmarried certificates, SKTM, SKCK, and crowd permit certificates. However, there are several obstacles faced in using this digital letter, there have been no updates and improvements, so the initial aim was to help, but instead it has become an obstacle to service. Apart from that, there needs to be communication and renewal of the MOU between the Malang City Government and the Ministry of Home Affairs regarding the authority to use dukcapil data so that data access can be achieved. NIK can be easier to use in the Suradi application.Keywords: Suradi application and administrative services.AbstrakSURADI adalah surat digital yang berfungsi sebagai alat informasi dalam Organisasi Perangkat Daerah Kota Malang. Selain itu, pada tingkat yang lebih luas, digunakan untuk mendukung digitalisasi layanan administrasi. Pembentukan sistem ini berakar pada Permendagri Nomor 6 Tahun 2011 tentang Naskah Kota Elektronik dalam Lingkungan Pemerintah. Surat digital dirancang untuk meningkatkan sistem naskah kota, menangani surat masuk dan keluar secara digital, dan mengoptimalkan pengelolaan surat di dalam pemerintah. Tujuan utama dari penelitian ini adalah untuk mengeksplorasi bagaimana aplikasi SURADI berkontribusi pada peningkatan layanan administrasi. Berdasarkan penelitian yang telah dilaksanakan, diperoleh kesimpulan bahwa digitalisasi pelayanan administrasi kelurahan melalui penerapan Suradi telah dilakukan dalam pengurusan surat seperti surat pengantar, surat pindah nikah, surat keterangan nikah, surat keterangan belum menikah, SKTM, SKCK, dan Surat keterangan ijin keramaian. Namun ada beberapa kendala yang dihadapi dalam pemakaian surat digital ini belum adanya pembaharuan dan penyempurnaan, sehingga tujuan awalnya adalah membantu malah menjadi penghambat pelayanan, selain itu perlu adanya komunikasi dan pembaharuan MOU antara Pemkot Malang dengan Kemendagri terkait wewenang penggunaan data Dukcapil sehingga akses data NIK bisa lebih mudah digunakan di aplikasi Suradi.